The neighborhood environment and its association with the spatio-temporal footprint of tobacco consumption and changes in smoking-related behaviors in a Swiss urban area. (July 2022) - Vallarta-Robledo, Juan R.; Marques-Vidal, Pedro; Sandoval, José Luis; De Ridder, David; Schaffner, Emmanuel; Humair, Jean-Paul; Cornuz, Jacques; Probst-Hensch, Nicole; Joost, Stéphane; Guessous, Idris
Abstract: This study aimed to evaluate the association of the neighborhood environment with the spatio-temporal dependence of tobacco consumption and changes in smoking-related behaviors in a Swiss urban area. Data were obtained from the CoLaus cohort (2003–2006, 2009–2012, and 2014–2017) in Lausanne, Switzerland. Local Moran's I was performed to assess the spatial dependence of tobacco consumption. Prospective changes in tobacco consumption and the location of residence of participants were assessed through Cox regressions. Analyses were adjusted by individual and neighborhood data. The neighborhood environment was spatially associated with tobacco consumption and changes in smoking-related behaviors independently of individual factors. Highlights: Individual and neighborhood inequalities exist in clusters of tobacco consumption. The neighborhood is associated with changes in tobacco consumption. The neighborhood is associated with residence changes that favor smoking behaviors. Policymakers should pay greater attention to the neighborhood environment.